1188 The association between work-family spillover and quality of sleep: a prospective study of japanese workers. (24th April 2018) - Hidaka, Yui; Shimazu, Akihito; Imamura, Kotaro; Iwata, Noboru; Shimada, Kyoko; Takahashi, Masaya; Tokita, Masahito; Watai, Izumi; Watanabe, Kazuhiro; Kawakami, Norito
Abstract : Introduction: Quality of Sleep has been linked to poor health. While work-family spillover is associated with health problems and impaired work performance of workers, previous findings were inconsistent on, the association between work-family spillover and sleep quality. No study was conducted in non-western countries. The objective of this study was to investigate the prospective association between work-family spillover and sleep quality among Japanese workers. Methods: The database used in the study was from a 2 year prospective cohort study. In the baseline survey (T1) in 2011, questionnaires were sent to 1356 workers living in two wards of Tokyo, and 753 (56%) responded, and 489 completed all scales and items used the study. A follow-up survey was conducted in 2013, with 224 (46%) respondents out of the 489 completers at T1; 176 completed all scales. The questionnaire (both T1 and T2) included self-reported instruments of work-family spillover (the Survey Work-home Interaction-NijmeGen, SWING), sleep quality (Pittsburgh Sleep Quality Index, PSQI), and job stressors (Brief Job Stress Questionnaire, BJSQ), and demographic variables (age, sex, education, marital status, and work styles). Multiple linear regression analysis was employed of PSQI scores on SWING scale scores, adjusting for demographic variables and PSQI score at T1. (SPSS version 22) Results: Among the 176 completers, 36% were men; the average age was 39 years old. Work to family negative spillover (beta=0.20) significantly and positively correlated with sleep quality, after adjusting for the demographic variables (p=0.020). No significant association was observed between the other type of spillover (i.e. work to family positive, family to work positive or negative) and sleep quality. (p>0.05). Conclusion: This prospective study confirmed the association between work-family negative spillover and sleep quality in a sample of Japanese workers. Work to family negative spillover could be considered a target condition to improve sleep quality of workers.